PROBLEMS AND SOLUTIONS OF HOME INDIVIDUAL EDUCATORS (Conference Zone, 2022)
In this article, the problems encountered in the pedagogical activity of a teacher teaching individually at home, the ways of working with students, based on scientific sources, are highlighted.